2009
DOI: 10.1099/jmm.0.004390-0
|View full text |Cite
|
Sign up to set email alerts
|

A mixture containing galactooligosaccharide, produced by the enzymic activity of Bifidobacterium bifidum, reduces Salmonella enterica serovar Typhimurium infection in mice

Abstract: The prebiotic Bimuno® is a mixture containing galactooligosaccharide, produced by the galactosyltransferase activity of Bifidobacterium bifidum NCIMB 41171 in the presence of lactose. Previous studies have implicated prebiotics in reducing infections by enteric pathogens, thus it was hypothesized that Bimuno® may confer some protection in the murine host from Salmonella enterica serovar Typhimurium (S. Typhimurium) infection. In this study, infection caused by S. Typhimurium SL1344nalr in the presence or absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 28 publications
2
71
2
1
Order By: Relevance
“…boulardii may mimic the host cell receptor to which the pathogen adheres (32,39). In that sense, Searle et al (28,29) showed that nondigestible oligosaccharides (NDOs) such as galactoligosaccharides reduce Salmonella in vitro adhesion and invasion in the human colonic HT-29-19A cell line and also in the ileum gut loop model in mice. Furthermore, S. cerevisiae var.…”
Section: Discussionmentioning
confidence: 99%
“…boulardii may mimic the host cell receptor to which the pathogen adheres (32,39). In that sense, Searle et al (28,29) showed that nondigestible oligosaccharides (NDOs) such as galactoligosaccharides reduce Salmonella in vitro adhesion and invasion in the human colonic HT-29-19A cell line and also in the ileum gut loop model in mice. Furthermore, S. cerevisiae var.…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotic-containing medium was removed and the wells were washed three times with HBSS. After washing, the cells were disrupted and the bacteria were enumerated as described above (Searle et al, 2009). …”
Section: Phenotypic Tests Of Plasmid Burden By Biolog Phenotypementioning
confidence: 99%
“…However, for ConA free glucose molecules present in this material could have partially contributed to the inhibitory effect. Although mannose is the primary ligand for Con A, this lectin also has affinity for glucose, but only about a fifth of that for mannose [30].…”
Section: Discussionmentioning
confidence: 99%